2018
DOI: 10.1242/dmm.032086
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of galectin-3 ameliorates the consequences of cardiac lipotoxicity in a rat model of diet-induced obesity

Abstract: Obesity is accompanied by metabolic alterations characterized by insulin resistance and cardiac lipotoxicity. Galectin-3 (Gal-3) induces cardiac inflammation and fibrosis in the context of obesity; however, its role in the metabolic consequences of obesity is not totally established. We have investigated the potential role of Gal-3 in the cardiac metabolic disturbances associated with obesity. In addition, we have explored whether this participation is, at least partially, acting on mitochondrial damage. Gal-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 62 publications
(75 reference statements)
4
21
0
Order By: Relevance
“…Ceramides are not only essential structural components of cell membranes, but also function as second messenger molecules in cell signaling, and have been implicated in different pathological settings [31][32][33]. The present data confirm previous observations, which support a negative effect of ceramides in insulin signaling in different tissues [16,33,34]. In addition, our data supports a role for ceramides in myocardial fibrosis, as well as hypertrophy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Ceramides are not only essential structural components of cell membranes, but also function as second messenger molecules in cell signaling, and have been implicated in different pathological settings [31][32][33]. The present data confirm previous observations, which support a negative effect of ceramides in insulin signaling in different tissues [16,33,34]. In addition, our data supports a role for ceramides in myocardial fibrosis, as well as hypertrophy.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, a correlation was found between mitochondrial TG levels and those of these proteins. Similar increases have been found and were associated with high cardiac lipid content, not only in the context of obesity, but also in that of diabetes and myocardial ischemia [5,16,24].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, the effect of Gal-3 on cardiac metabolic disturbance associated with obesity has been investigated. Marín-Royo et al found that Gal-3 inhibition attenuated the consequences of cardiac lipotoxicity induced by high-fat diet in vivo [16]. Therefore, Gal-3 might exacerbate atherosclerosis plaque through promoting endocytosis of lipoprotein and disturbing lipid metabolism.…”
Section: Gal-3 In Macrophage Differentiation and Foam Cellmentioning
confidence: 99%
“…As an important inflammatory biomarker, Gal-3 can promote the secretion of other proinflammatory factors like tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) through activation of macrophages in a dose-dependent manner [15]. Gal-3 also participates in the progression of lipid endocytosis, cell apoptosis, cell differentiation, cell adhesion, and tumor metastasis [16][17][18].…”
Section: Introductionmentioning
confidence: 99%